2013
DOI: 10.1016/j.wasman.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biodegradation at the Landgraaf bioreactor test-cell

Abstract: From 2001 to 2011, a bioreactor demonstration was performed in a 25,000m(3) (8m deep, 3500m(2) surface) test-cell. In this bioreactor, biodegradation was enhanced by premixing and homogenizing of waste, recirculation of leachate and aeration. Anaerobic biodegradation was completed within four years and was followed by two years of aeration. Ultimately a residue was obtained that had lost approximately 95% of its biogas potential. Biodegradation resulted in a significantly reduced leaching potential for dissolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
(13 reference statements)
1
8
0
1
Order By: Relevance
“…For example, increasing the number of individually operated and controlled landfill cells and consequently reducing W in each cell would lower t max and accelerate k in the cell. Similar to the discussion in Section 3.6, a few studies have demonstrated effective reduction in t max values, which approached those achieved in laboratory experiments (Budka et al 2007;Yazdani et al 2012;Oonk et al 2013). In addition, changing B 0 (%) in landfilled waste appears to have a lower impact than reducing W on reducing t max for landfill cells.…”
Section: Comparison Of T Max Between Landfills Laboratory Experimentsupporting
confidence: 59%
See 3 more Smart Citations
“…For example, increasing the number of individually operated and controlled landfill cells and consequently reducing W in each cell would lower t max and accelerate k in the cell. Similar to the discussion in Section 3.6, a few studies have demonstrated effective reduction in t max values, which approached those achieved in laboratory experiments (Budka et al 2007;Yazdani et al 2012;Oonk et al 2013). In addition, changing B 0 (%) in landfilled waste appears to have a lower impact than reducing W on reducing t max for landfill cells.…”
Section: Comparison Of T Max Between Landfills Laboratory Experimentsupporting
confidence: 59%
“…These include reduction of waste heterogeneity, improvements on the addition, distribution, and migration of moisture in waste, and increased gas collection efficiencies. Some of the potential improvements mentioned previously have been implemented in a few studies and demonstrated very promising increases in k values, which approached those achieved in laboratory experiments (Budka et al 2007;Yazdani et al 2012;Oonk et al 2013). As suggested by Eqn.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…A novel approach to landfill after-care has seen a focus on the accelerated stabilization of wastes under controlled conditions within in the time frame of current liability using in-situ techniques such as aeration and/or (re-)infiltration of water or leachate. Both techniques aim to decrease a landfill's emission potential by accelerating the decay of reactive organic matter to expedite the attainment of stable conditions in the waste (Kosson et al, 2002;Scharff et al, 2011;van der Sloot et al 2017) and environmentally acceptable residual emissions (Brandstätter et al, 2015a,b, Heyer et al, 2005Oonk et al, 2013;Reinhart et al, 1996Reinhart et al, , 2002Ritzkowkski et al, 2006). These are reached when the water leaving the landfill complies with soil and groundwater quality criteria and can therefore be safely received by soil, ground-and surface waters.…”
Section: Introductionmentioning
confidence: 99%